Translating preclinical models of neuronal ceroid lipofuscinosis: progress and prospects. (2nd September 2017) - Nelvagal, Hemanth R.; Cooper, Jonathan D.
ABSTRACT: Introduction : The Neuronal Ceroid Lipofuscinoses (NCLs, or Batten Disease) are a group of distinct inherited neurodegenerative Lysosomal Storage Disorders (LSDs) that mainly affect children and young adults. Despite recent advances, these are fatal and profoundly disabling disorders for which there remains a pressing need to devise curative therapies. Areas covered : This article details the advances from new preclinical models of the NCLs, together with progress in developing experimental therapeutic strategies and in translating these advances into clinical trials. Expert opinion : Animal models have been crucial for improving the understanding of the pathological mechanisms in each form, and for testing experimental therapies. With the relative success of some pre-clinical experimental approaches, several clinical trials have been initiated. These have had varying degrees of success, but the recent FDA approval of recombinant enzyme replacement for CLN2 disease, an approach initially tested in mouse and dog models, is a positive step towards the goal of effective therapies for the NCLs. As new data emerges from preclinical models about NCL pathogenesis, it is increasingly likely that a combination of therapies that either target different regions of the body, or multiple disease mechanisms, will be required to effectively treat the NCLs.